Repeated cardiac arrest caused by an air embolism during hepatic resection: A case report. Issue 39 (September 2018) - Luo, Li-Hui; Peng, Zhi-You; Zhu, Sheng-Mei; Yao, Yong-Xing
Abstract: Rationale: Although venous air embolism (VAE) during liver operation has been reported occasionally, fatal VAE in hepatic resection is uncommon. Prompt detection of VAE by transesophageal echocardiography (TEE) is crucial for effective therapy. We describe a case of fatal VAE that caused repeated cardiac arrest during hepatic resection and was confirmed by TEE. Patient concerns: A 51-year-old woman with a body weight of 50 kg underwent partial liver resection due to intrahepatic duct calculus. She had a 1-year history of intrahepatic duct calculus without cardiopulmonary disease. The operation was performed under general anesthesia combined with epidural block. When the inferior vena cava was compressed, the Pet CO2 level decreased abruptly from 30 to 10 mmHg, followed by a decrease in SpO2 and the development of hypotension. Her heart rate increased with ST interval elevation on electrocardiography monitoring. Ephedrine and phenylephrine were administered immediately but had little effect. Cardiac arrest occurred. Diagnoses: Air embolism was detected by TEE. Interventions: Resuscitation was successful although cardiac arrest occurred repeatedly. Outcomes: The patient returned to consciousness 6 hours postoperatively but died of multiorgan dysfunction 10 days later. Lessons: Fatal air embolism may happen during hepatic resection. Prompt detection of VAE by TEE is crucial for effective therapy and should always be available during hepatic resection.